Pengembangan Karakter Melalui Pendekatan Terpadu untuk Meningkatkan Kreativitas Siswa Sekolah Dasar - Malik, Husni (Jurnal Didaktika Pendidikan Dasar, 2020)
Programmed character education, teacher facilitator character planting requires innovation and habituation in the KBM. The 2013 curriculum develops Strengthening Education Karaketr (PPK), the National Literacy Movement (GLN), 21st Century Learning and High-Level Thinking through aspects of skills and knowledge. Character education can be developed through the RPP approach that is packaged through the activities of Study, Exploration, Formulate, Present, Apply, World, Ukhrowi (TERPADU). Student learning outcomes and creativity of grade VI SDIT Nur Hidayah Surakarta are still relatively low and need to be optimized. Character development through TERPADU approach is used by the writer to overcome these problems. Innovation is more focused on improving creativity and learning outcomes of theme 1 learning 1 and 3 (BI, Natural Sciences and Social Sciences) grade VI students. Observer observation during the learning process of the development and character formation of learning activities both creativity and results. The results showed that student activity increased from 78.09% to 87.6% with a very good predicate. Learning outcomes (KI 3) have increased completeness for each BI, Natural Sciences and Social Sciences subjects from 77%, 69%, and 33% to 100%. Increased completeness of the aspects of student skills (KI 4) assessed through rubrics with the percentage of each subject of BI, Natural Sciences and Social Sciences that is 69%, 89% and 81% to 100%. The effect of completeness is a positive impact on student activity, which can be seen from the responses of students through questionnaires, there was an increase from 69.92% to 83.29%. The development and formation of character through TERPADU class VI themes 1 learning 1 and 3, have a positive influence on improving student creativity and learning outcomes.